2022
DOI: 10.1177/19418744221105961
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Manifestations and Creatine Kinase in COVID-19

Abstract: Background and Purpose Skeletal muscle symptoms and elevated creatine kinase (CK) levels have been consistently reported as part of the COVID-19 disease process. Previous studies have yet to show a consistent relationship between CK levels and skeletal muscle symptoms, disease severity, and death from COVID-19. The purpose of this study is to determine whether elevated CK is associated with a COVID-19 course requiring intubation, intensive care, and/or causing death. Secondary objectives: To determine if there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
4
4
0
Order By: Relevance
“…Muscle pain and fatigue are common manifestations of patients with COVID‐19 infection, and increased CK may predict a worse COVID‐19 outcome 39 . Similar to other published studies, 40,41 we found that the CK value for patients with severe COVID‐19 was higher than patients with mild disease.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Muscle pain and fatigue are common manifestations of patients with COVID‐19 infection, and increased CK may predict a worse COVID‐19 outcome 39 . Similar to other published studies, 40,41 we found that the CK value for patients with severe COVID‐19 was higher than patients with mild disease.…”
Section: Discussionsupporting
confidence: 88%
“…Muscle pain and fatigue are common manifestations of patients with COVID-19 infection, and increased CK may predict a worse COVID-19 outcome. 39 Similar to other published studies, 40,41…”
Section: Variables Selection Using Machine Learning and Web Developme...supporting
confidence: 86%
“…Contrary to the low incidence of cardiovascular complications, we frequently observed COVID-19 patients with elevated cardiac biomarkers: hsTnI≥99% ile in 24.6%, NT-proBNP≥125 pg/mL in 35.7%, CK>UNL in 25.9% and CK-MB>UNL in 11.8%. Former reports indicated similar rates of COVID-19 patients with elevated biomarker values: troponin, 6.5%–36%, BNP or NT-proBNP, 13%–49%, CK, 12%–46% and CKMB, 5.1%–11% 4–6 16 17. Consistent with the current study, patients with elevated cardiac biomarkers had a significantly higher incidence of mortality than those without cardiac biomarker elevation.…”
Section: Discussionsupporting
confidence: 87%
“…We did not find an association between skeletal muscle injury and severity of COVID‐19. Other authors have also reported such a lack of association 1,20–22 …”
Section: Discussionmentioning
confidence: 95%
“…Other authors have also reported such a lack of association. 1,[20][21][22] Demonstrable muscle weakness, particularly of neck flexor muscles, and disability that limits daily activities were common. Very few studies have documented formal evaluation of muscle weakness in acute settings and none exist for acute COVID infections.…”
Section: Discussionmentioning
confidence: 99%